Drusen and Photoreceptor Abnormalities in African-Americans with Intermediate Non-neovascular Age-related Macular Degeneration. (9th June 2014) - Sadigh, Sam; Luo, Xunda; Cideciyan, Artur V.; Sumaroka, Alexander; Boxley, Stacy L.; Hall, Laura M.; Sheplock, Rebecca; Feuer, William J.; Stambolian, Dwight S.; Jacobson, Samuel G.
Abstract: Purpose/Aim : To investigate the relationship of drusen and photoreceptor abnormalities in African-American (AA) patients with intermediate non-neovascular age-related macular degeneration (AMD). Materials and methods : AA patients with intermediate AMD ( n  = 11; age 52–77 years) were studied with spectral-domain optical coherence tomography. Macular location and characteristics of large drusen (≥125 µm) were determined. Thickness of photoreceptor laminae was quantified overlying drusen and in other macular regions. A patient with advanced AMD (age 87) was included to illustrate the disease spectrum. Results : In this AA patient cohort, the spectrum of changes known to occur in AMD, including large drusen, sub-retinal drusenoid deposits and geographic atrophy, were identified. In intermediate AMD eyes ( n  = 17), there were 183 large drusen, the majority of which were pericentral in location. Overlying the drusen there was significant thinning of the photoreceptor outer nuclear layer (termed ONL + ) as well as the inner and outer segments (IS + OS). The reductions in IS + OS thickness were directly related to ONL + thickness. In a fraction (∼8%) of paradrusen locations with normal lamination sampled within ∼280 µm of peak drusen height, ONL + was significantly thickened compared to age and retinal-location-matched normal values. Topographical maps of the macula confirmed ONL thickening in regions neighboring and distant to large drusen. Conclusions : We confirm there is a pericentral distribution of drusen across AA-AMD maculae rather than the central localization in Caucasian AMD. Reductions in the photoreceptor laminae overlying drusen are evident. ONL + thickening in some macular areas of AA-AMD eyes may be an early phenotypic marker for photoreceptor stress.